1996
DOI: 10.1093/intimm/8.3.367
|View full text |Cite
|
Sign up to set email alerts
|

H2-M3wt-restricted, Listeria monocytogenes-specific CD8 T cells recognize a novel, hydrophobic, protease-resistant, periodate-sensitive antigen

Abstract: Mice infected with Listeria monocytogenes (LM) generate H2-M3wt-restricted CD8 effectors which recognize a heat-killed LM-associated antigen (HAA) presented by macrophages. To characterize HAA, we extracted a bioactive component from LM using SDS or NaOH. Extracted HAA aggregated in hydrophilic solvents but dissociated in the presence of SDS into a smaller subunit which migrated in Sephadex G-200 between chymotrypsinogen (25 kDa) and cytochrome c (12.5 kDa). HAA bioactivity and size was unaffected by proteinas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

1996
1996
2003
2003

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 39 publications
1
27
0
Order By: Relevance
“…Substantial protection was observed following transfer of 3C8 cells to Listeria-infected mice. Similar results were obtained by Nataraj et al using an H2-M3-restricted clone generated following in vitro stimulation with HKL (23). The strength of the protection mediated by 3C8 cells was further demonstrated by the ability to rescue mice from a lethal infection.…”
Section: Discussionsupporting
confidence: 83%
“…Substantial protection was observed following transfer of 3C8 cells to Listeria-infected mice. Similar results were obtained by Nataraj et al using an H2-M3-restricted clone generated following in vitro stimulation with HKL (23). The strength of the protection mediated by 3C8 cells was further demonstrated by the ability to rescue mice from a lethal infection.…”
Section: Discussionsupporting
confidence: 83%
“…Glycolipid bacterial Ags may induce cytolytic activity by H2-M3-restricted CD8 ϩ T cells (15). To prove that other peptides, rather than lipids or glycolipids, primed fMIGWII-specific CD8 ϩ T cells during infection with L. monocytogenes fMIG neg , we subjected HPLC fractions from L. monocytogenes fMIG neg culture supernatants that induced the strongest cytolytic activity to enzymatic digestion.…”
Section: Discussionmentioning
confidence: 99%
“…However, the heat-killed L. monocytogenes-associated Ag was reported to be highly protease resistant, but periodate sensitive, suggesting that it contains a carbohydrate component (15). Subsequently, it was shown that the heat-killed L. monocytogenes-associated Ag consists of a complex of immunogenic fMIGWII associated with bacterial cardiolipin A (34).…”
Section: Fmigwii-specific Cd8 ϩ T Cells Are Also Primed By Peptides Wmentioning
confidence: 99%
See 1 more Smart Citation
“…CD4 Ab had minimal effect on the response of LCD4.1 or LCD4.3 to M. leprae (Fig. 8, A and B), whereas the Ab inhibited the proliferation of an HLA-DRrestricted T cell line, D103-5 (45,46), by 83% (Fig. 8C).…”
Section: Cd1-restricted T Cellsmentioning
confidence: 98%